Logistic Supply Chain Management and Economic Security of the Enterprise - M. P. Vlasov (International Journal of Supply Chain Management, 2020)
Abstract- In recent years, the interdisciplinary research of supply chains and economic security has received extensive, yet gradual, attention; when compared to the rapid economic growth of the service industry, however, sustainable supply chain management has not been systematically explored yet. The security issue in supply chains is among the most pressing concerns that firms are currently facing. So the purpose of this article is to formalize the process of interaction between an enterprise and suppliers of components necessary for the production of products. The process is considered from the point of view of determining the best conditions for the operation of the enterprise under which the production of all planned products is ensured and the costs of the enterprise for the acquisition of components necessary for the production are minimized. The model reflects the unambiguous dependence of purchases on the range and volume of output. Typically, when simulating supply chain processes, the emphasis is on managing the inventory of components of one item on the one hand or on minimizing the cost of shipping only one component. With this approach, the costs of the enterprise as a whole usually fall out of consideration. The proposed economic and mathematical model establishes a close interdependence between the proceeds from the sale of products and the costs of acquiring the components necessary for the production, between the capabilities of suppliers and the needs of the enterprise, in a supply chain model. In this model, emphasis is placed on ensuring the reliability of supplies, their magnitude and timeliness, which should be stipulated in contracts for the supply of necessary components. The model implicitly takes into account the presence of accounts payable, which may affect the amount of funds allocated for the purchase of components necessary for the production. The advantages of the model should also include accounting for the availability of components at the time of procurement. As an additional effect of the application of the model, the possibility of minimizing working capital through the implementation of a sound logistics policy based on existing working capital and their use to ensure timely delivery in the required volumes of components is considered. The supply chain ensures the economic security of the enterprise. The effective use of working capital contributes to an increase in the profitability of the enterprise and, as a result, to an increase in the income of the owner.